THE EFFECT OF COMPANY PROFIT ON STOCK PRICE BEFORE AND AFTER COVID-19 IN THE INFRASTRUCTURE SECTOR LISTED ON THE INDONESIA STOCK EXCHANGE - Stanly W Alexander; Claudia W M Korompis (Universitas Sam Ratulangi, 2023)
The research objective is to compare the effect of company profits on stock prices in the infrastructure sector listed on the Stock Exchange for the 2018-2021 period. The research method used is the archival method with a quantitative research type. Researchers used the population of all infrastructure sector companies listed on the Indonesia Stock Exchange as research data with 46 companies. The research data is divided into two: the company's financial statements before Covid-19, namely 2018-2019 and the company's financial reports during Covid-19, namely 2020-2021. The study's results show that both before the Covid-19 period and when Covid-19 occurred, company profits were a factor that significantly influenced stock prices.